Behavioral variation across multiple phases of intravenous cocaine self-administration among genetically diverse mouse populations - Price E. Dickson; Udita Datta; Troy D. Wilcox; Ashley A. Auth; Robyn L. Ball; Matt Dunn; Heidi S. Fisher; Alyssa Klein; Michael R. Leonardo; Tyler A. Roy; Michael C. Saul; Jason A. Bubier; et al. (Psychopharmacology, 2026)
Genetic and other predisposing factors can influence the progression from initiation of drug intake to compulsive substance use through distinct biobehavioral processes. Operant cocaine self-administration studies in laboratory mice offer a powerful method to dissect the biology of this progression from initiation, dose-response, extinction, and cued reinstatement in a controlled, tractable system. However, many such studies encompass limited genetic diversity and rarely examine self-administration behaviors beyond the acquisition stage. Here, we study three high-diversity mouse populations – 50 strains from the Collaborative Cross (CC) reference panel, a large sample of Diversity Outbred (J: DO) population and their eight founder strains – to characterize the varied phenotypic manifestation of behaviors across multiple phases of cocaine intravenous self-administration (IVSA) in both sexes. We observed distinct strain differences among the founders and CC strains in all phases of self-administration, with heritability estimates ranging from 0 to 0.585 and many CC and J: DO phenotypic values exceeding the range of founders including the C57BL/6J strain. Sex differences were common across behaviors, some manifesting as main effects, others as strain interactions. Finally, by adopting a multi-stage design, we identified extreme strains for various cocaine intake and response traits. Together, these findings demonstrate the utility of extended self-administration protocols in high-diversity mouse populations and establish feasibility for their use in the discovery and characterization of biological mechanisms of substance use traits and for preclinical studies in relevant, complex mouse models.